Reports of the International Organization for Migration: Analysis of the Problems of Ukrainian Refugees and Internally Displaced Persons in the context of the Large-Scale Russian Invasion of Ukraine - Zakirova Svitlana (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
Russia’s full-scale military aggression against Ukraine caused a wave of forced dis placement of Ukrainian citizens that was extraordinary in its consequences and scale. The article presents the study of special publications of the International Organization for Migration (IOM) regarding the general surveys of the Ukrainian population after the beginning of the large-scale Russian invasion of Ukraine. The research analyzes the structure and topics of reports and surveys of the IOM, characterizes the features of the studied publications, determines the possibilities of using the presented materials of the IOM for research of the problems of Ukrainian refugees and internally displaced persons. The methodology of the conducted research of IOM reports and surveys is based on the use of problem-chronological, statistical, comparative and other methods of scientific analysis. The author has proposed a classification of the analyzed IOM editions: according to territorial characteristics - international, national, regional and local; according to the regularity and repeatability of the research - periodic and episodic; according to the target audience of respondents - research on 1) Ukrainian refugees abroad, 2) internally displaced persons, 3) universal; according to the range of analyzed issues - thematic and complex. Documents based on the results of IOM surveys have a logical structure, contain certain “mandatoryˮ sections that reveal the main indicators of the results obtained, on the basis of which thorough conclusions are formed. It is noted that the systematicity of approaches and methods, comprehensiveness and diversity of information turns IOM analytical reports and materials into an important source for further study of the problems of refugees and displaced persons, creates a basis for the preparation of specific recommendations and the development of systematic approaches in order to develop a strategy to overcome the negative consequences of forced resettlement at the state and local levels.